Prospects of Using Blockchain Technology in the Organization of the Transportation Process and Supply Chain - Mukhamedova, Ziyoda; Mukhamedova, Dilbar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The spread and formation of information technologies is a fact in the modern world. Over the past decades, this direction has determined the main trajectories of the development of the economy, industry and society as a whole, which in turn leads to enormous changes in the aspect of technological progress. The formation and development of the digital environment is one of the top priorities of most developed countries, including the Russian Federation, the USA, Germany and others. Modern technological progress is characterized by the development and formation of various information technologies that contribute to improving the rational resources’ use and enhancing the competence of modern enterprises. To date, there are a huge number of applied and professional tasks, the most effective solution of which involves the use of various kinds of information technologies. This article raises the question of the relevance of using Blockchain technology, possible problems of its implementation, as well as what blockchain can give to different economy and logistics sectors. To understand how the "blockchain" works, we take as a basis the second-generation blockchain "Ethereum", which includes an updated system of smart contracts and much more. Topical issues that blockchain can solve in logistics, such as inventory and cargo tracking, authentication, transparency in supply chains, increasing the speed of cargo delivery, and the creation of a freight market, are considered. The possibility is also considered and a description of the application of this technology on the railway network of Uzbekistan is given. This technology is applicable in many sectors of the modern rapidly developing world and is able to speed up the growth of the digital economy.